The impact of life events on depression among elderly in Kelantan - Abdullah, Nor Ilyani (2018)
Background: Life events are believed to be associated with the development of depression. The extended years of living will invariably subject the elderly people to more life events. Thus, they are more vulnerable to suffer from depression. The aim of this study is to determine the prevalence of depression among the elderly residents in Kelantan and to elucidate the association between life events and the elderly depression. Methods: This is a cross sectional study, which was conducted in Kelantan from April 2016 until December 2017. Stratified random sampling method was used to recruit 422 elderly people aged 60 years and above. The Malay Geriatric Depression Scale-15 (M-GDS-15) was utilized to identify the presence of depression, while life events occurring in the past twelve months were evaluated using the Social Readjustment Rating Scale (SRRS). Data were analyzed using simple and multiple logistic regressions. Results: The prevalence of depression among elderly in Kelantan is 22%. Being older elders (aged more than 75) and staying in traditional house were found to have positive association with depression, while being married and performing exercise were identified as the protective factors against depression. The significant life events that contributed to elderly depression were death of spouse (95% CI =1.45, 26.34, p=0.014), changes of social activities (95%CI: 2.24,6.91, p<0.001), serious illness orinjuries (95% CI =1.15,7.84, p=0.025), changes of life habits (95%CI: 1.50,4.73, p=0.001), changes of sleeping habits (95% CI: 1.38,4.70,p=0.003), changes of lifestyle (95%CI: 1.32,4.61,p=0.005) and changes of numbers of family get-together (95% CI: 1.32,4.07,p=0.004). Conclusion: The prevalence of depression among elderly in Kelantan is high. The changes in social relationship, activities and lifestyles are significantly related with elderly depression. These life events are inevitable in elderly. Therefore, there is a need to detect early signs of depression especially in those who faced certain amounts of recent life events. Social interventions such as promoting healthy and active lifestyle among elderly also warrant attention.